THE PERFORMANCES IN THE SYSTEM OF THE INTELLECTUAL PROPERTY LAW - Ayvazyan, Mariam (State and Law, 2022)
The article studies the role of the performances in the Intellectual Property law system. For decades there has been an ongoing debate on whether the performances should be protected by copyright or related rights. Hence, the article starts the discussion by exploring the criteria for copyright protection. It concludes that the performances have necessary features to be eligible for copyright protection. However, it is preferable to keep the current status quo and protect the performances in the framework of the related rights system considering the unique peculiarities of the performance. Additionally, the article points out the cases when performances can be protected both by the copyright and related rights.